2007
DOI: 10.1099/mic.0.2007/008524-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface characteristics of the entomopathogenic fungus Beauveria (Cordyceps) bassiana

Abstract: Marked differences in surface characteristics were observed among three types of single-cell propagules produced by the entomopathogenic fungus Beauveria bassiana. Atomic force microscopy (AFM) revealed the presence of bundles or fascicles in aerial conidia absent from in vitro blastospores and submerged conidia. Contact angle measurements using polar and apolar test liquids placed on cell layers were used to calculate surface tension values and the free energies of interaction of the cell types with surfaces.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 158 publications
(106 citation statements)
references
References 47 publications
6
93
0
7
Order By: Relevance
“…Studies on the adhesion of submerged conidia and blastospores have revealed that the former cells are able to bind a diverse range of substrata, including hydrophobic, weakly polar and hydrophilic surfaces, whereas the latter cells display some binding to weakly polar substrata but strong binding to hydrophilic surfaces (Holder & Keyhani, 2005). The relationship between the loss of fucose residues and the observed surface properties of submerged conidia is difficult to evaluate; however, the loss of multiple carbohydrate epitopes that might mask charged residues on the surface of in vitro blastospores as compared with aerial conidia is consistent with the idea that electrostatic charge plays a significant role in adhesion of these cells (Holder et al, 2007).…”
Section: B Bassiana Surface Carbohydratessupporting
confidence: 62%
See 2 more Smart Citations
“…Studies on the adhesion of submerged conidia and blastospores have revealed that the former cells are able to bind a diverse range of substrata, including hydrophobic, weakly polar and hydrophilic surfaces, whereas the latter cells display some binding to weakly polar substrata but strong binding to hydrophilic surfaces (Holder & Keyhani, 2005). The relationship between the loss of fucose residues and the observed surface properties of submerged conidia is difficult to evaluate; however, the loss of multiple carbohydrate epitopes that might mask charged residues on the surface of in vitro blastospores as compared with aerial conidia is consistent with the idea that electrostatic charge plays a significant role in adhesion of these cells (Holder et al, 2007).…”
Section: B Bassiana Surface Carbohydratessupporting
confidence: 62%
“…However, it is unclear whether the carbohydrates detected would contribute to the net negative surface charge of aerial conidia at neutral pH (Holder et al, 2007), particularly since little to no sialic acid, which would contribute to the surface charge, was detected. Studies on the adhesion of submerged conidia and blastospores have revealed that the former cells are able to bind a diverse range of substrata, including hydrophobic, weakly polar and hydrophilic surfaces, whereas the latter cells display some binding to weakly polar substrata but strong binding to hydrophilic surfaces (Holder & Keyhani, 2005).…”
Section: B Bassiana Surface Carbohydratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungal spores (conidia) of the insect pathogenic fungus, B. bassiana, will attempt to attach and initiate infection essentially anywhere on host cuticle, although preferential infection sites on some hosts have been observed (21,49,50). The infection program is initiated by surface cues, and the fungus is capable of assimilating long-chain alkanes and other lipids that are often found as major constituents of the insect epicuticle (41).…”
Section: Discussionmentioning
confidence: 99%
“…Infection by M. anisopliae and B. bassiana begins when the fungal conidium contacts the insect cuticle, initiating the expression of genes involved in cuticle adhesion and degradation (Holder & Keyhani, 2005;Cho et al, 2006a, b;Holder et al, 2007). The conidium germinates and the fungal hyphae transgress the insect cuticle, gaining access to the insect haemolymph.…”
Section: Introductionmentioning
confidence: 99%